The Role Brand Image and Location on Buying Interest Instagram Social Media at Coffee Shop in Tangerang City: (Case Study of Kala Coffee & Eatery and Kedai Seruput) - Pratama, Putra; Daenulhay, Daenulhay; Muttaqijn, Imam (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This study aims to find out determine the number of influence of the variable brand image, location, on buying interest through instagram social media at Coffee Shops in Tangerang City. The method of this study is quantitative, with respondents all consumers Coffee Shop Tangerang City Case Study in Kala Coffee & Eatery and Kedai Seruput, which numbered 100 persons. The technique analysis used is simple and multiple linear regression analysis, with hypothesis testing methods, namely t-test and F-test. The results of hypothesis testing state that partially or simultaneously Brand Image, Location, and Buying Interest variables positive and significant effect on the Instagram Social Media variable, with the number of influence of each partial effect being 24% and 19%. However, the magnitude of the simultaneous influence on the independent variable on Purchase Interest is 46.6%, while the remaining 53.4% "‹"‹is influenced by other factors not examined in this study. The influence of Brand Image and Location using the role of Social Media effectively affects consumer buying interest will increase.